Assistance in obtaining the marketing authorization for the home food industry of Omah Kripik Mbote - Muhammad Luthfi; Dwi Ratna Indri Hapsari (Universitas Muhammadiyah Magelang, 2024)
Omah Kripik Mbote, one of the household food industry (IRTP), encounters challenges in acquiring distribution permits, a crucial step in initiating an IRTP business. One major hurdle is the lack of comprehension and knowledge regarding the permit processing procedures. To address this issue, assistance was provided to facilitate the acquisition of an IRTP marketing authorization for Omah Kripik Mbote. This assistance aims to offer a comprehensive understanding of the procedures involved in obtaining an IRTP marketing authorization and processing a Home Industry Food Production Certificate (SPP-IRT) for Omah Kripik Mbote. The approach utilized in this assistance includes both classical and individualized methods, focusing on: a) disseminating information about the procedures for obtaining IRTP marketing authorization; b) aiding in identifying the requirements for acquiring IRTP marketing authorization; and c) guiding through the process of obtaining IRTP marketing authorization. As a result of this assistance, Omah Kripik Mbote has gained a better grasp of the procedures for obtaining IRTP marketing authorization, along with the issuance of SPP-IRT with PIRT numbers.